The Existence of Mangandung Tradition in Wedding Ceremony of Angkola Society - ., Hennilawati; Diana, S (KnE Social Sciences, 2018)
The existence of mangandung tradition in wedding ceremony of Angkola society was oral tradition review that existed in Angkola ethnic. This tradition was existed in wedding ceremony before pasahat boru procession. Systematically, mangandung was occurred after mangupa and before pasahat boru in the tradition procession. The mangandung procession was acted by mothers through touching sobs because bride would go away from her family to have new family from her husband. This review conducted by using culture concept that related to oral tradition. Anthropology approach based on culture was used to review old tradition that existed in the local society. It indicated that the researcher wanted to look the process of inheriting about mangandung tradition as well as mythology symbols and mindset of Angkola society. Archetype approach by Jung was appropriate approach to review issue about the inheriting of old culture that have correlation between psychology and anthropology of literatures. Qualitative method based on naturalistic was research method that used to review the existed phenomena. Based on the findings, there was existence of mangandung tradition in wedding ceremony in Angkola society but it got culture diffusion, namely the old tradition of mangandung consisted with touching advices changed to new tradition of mangandung that filled with touching musical and melody. Keywords: Mangandung, Wedding Ceremony, Angkola Society